The Prescription Pattern And Rationality Of Antibiotics Usage In General Surgery Polyclinic Patient At RSD Kalisat In October - December 2020 - CHURORI RORIK CAHYONO (AKADEMI FARMASI JEMBER, 2021)
ABSTRACTBackground research: Antibiotics are the most widely used drug class in the world due to the high incidence of bacterial infections. The high use of antibiotics but not balanced with the rational use of antibiotics can have a negative impact, one of which is resistance. Objective: This study was conducted to examine the prescribing pattern and rationale for the use of antibiotics in the Kalisat Jember Hospital. Research method: This study used a descriptive design, data collection was carried out retrospectively which was taken from October to December 2020 at the surgical clinic at the Kalisat Jember area hospital. Result and coclusion: Based on the calculation results, the number of samples used in this study were 263 prescription sheets with antibiotics. From the results of the study, it was found that the most prescribed pattern of antibiotic prescribing was cefixime as many as 165 prescriptions (62.74%) and the most antibiotic preparations prescribed in tablet form were 253 prescriptions (96.20%). From the results of the study, it was also found that the rationality of the use of antibiotics, namely the accuracy of the dose of 100%, the accuracy of the frequency of 99.24% and the accuracy of the duration of 100%.Keywords: Antibiotic, rational, prescription